2010
DOI: 10.1007/s10545-010-9047-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic approaches for neuronopathic lysosomal storage disorders

Abstract: Therapy of the central nervous system (CNS) manifestations of lysosomal storage diseases (LSDs) has remained a major challenge because of its inability to deliver therapeutic agents efficiently across the intact blood-brain barrier. Non-specific therapies such as hematopoietic stem cell transplantation have been useful in globoid cell leukodystrophy (Krabbe disease) and in some mucopolysaccharidoses. Anti-inflammatory agents also show promise as adjuvant therapy. High doses of replacement therapy with native o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 79 publications
(87 reference statements)
0
30
0
1
Order By: Relevance
“…Moreover, additional therapeutic approaches such as chemical chaperone therapy, substrate reduction therapy, gene therapy, and stop codon read-through are in use in clinical trials, furthering interest in NBS for LSDs. [5][6][7] An additional argument for inclusion of at least some LSDs in NBS has been the relative prevalence of these conditions, which for most conditions has been shown to be more frequent than previously expected. For example, pilot NBS studies for Fabry disease in Italy and in Taiwan revealed surprisingly high incidences (approximately 1:3100 and 1:1250 male newborns, respectively 8,9 ).…”
Section: Newborn Screening For Lysosomal Storage Disorders (Lsds)mentioning
confidence: 99%
“…Moreover, additional therapeutic approaches such as chemical chaperone therapy, substrate reduction therapy, gene therapy, and stop codon read-through are in use in clinical trials, furthering interest in NBS for LSDs. [5][6][7] An additional argument for inclusion of at least some LSDs in NBS has been the relative prevalence of these conditions, which for most conditions has been shown to be more frequent than previously expected. For example, pilot NBS studies for Fabry disease in Italy and in Taiwan revealed surprisingly high incidences (approximately 1:3100 and 1:1250 male newborns, respectively 8,9 ).…”
Section: Newborn Screening For Lysosomal Storage Disorders (Lsds)mentioning
confidence: 99%
“…Enzyme replacement therapy (ERT) using recombinant enzyme, which is designed to be incorporated by the mannose 6-phosphate (M6P) receptor and targeted to lysosomes, is available in some lysosomal storage disorders such as Fabry disease, Gaucher disease, Pompe disease, and various mucopolysaccharidoses, whereas many other therapies that enhance enzyme activities or reduce substrates are undergoing clinical trials for many different lysosomal storage disorders (7)(8)(9)(10)(11)(12)(13). In the case of ML-II, however, there is no ERT to date as lysosomes lack dozens of enzymes targeted by the M6P receptor-dependent pathway.…”
mentioning
confidence: 99%
“…SRT is based on the concept that the inhibition of specific steps of the biosynthetic pathways of substrates may reduce their flux to lysosomes and help restore the equilibrium between their synthesis and catabolism (48,49). This task is generally accomplished by using small-molecule inhibitors of enzymes involved in the biosynthesis of substrates.…”
Section: Substrate Reduction Therapymentioning
confidence: 99%